Food Price Increases and Net Food Importing Countries : Lessons from the Recent Past - Ng, Francis; Aksoy, M. Ataman (2012)
Recent increases in food and other commodity prices have highlighted concerns that many poor countries are net food importers and higher food prices would worsen their trade balances. In this article, we analyze the changes in food trade balances associated with the 32% increase in food prices from 2000/2001 to 2004/2005. We find a small deterioration in food trade balances of low-income countries and an improvement in middle-income countries. The deterioration is most severe for countries in conflict and small island states, so attention should be placed first on these countries and on a few very-low-income countries that are also vulnerable. Because low-income countries as a group had much lower agricultural GDP growth rates than middle-income countries, the answers to food vulnerability in low-income countries should probably be addressed within the context of incentives for agricultural production.